calculati.
a)(x-2)(x+2)-(x+2)²
b(4a-3b)²+(4a+3b)²-(4a+3b)(4a-3b)
c)(2a+b)²-(2a-b)²-(3a+b)(3a-b)
d)(3-2a)²-(4a+1)²+(4a-5)(4a+5)
Răspunsuri la întrebare
Răspuns de
2
a) x²+2x-2x-4-(x²+4x+4)=
=x²+2x-2x-4-x²-4x-4= -4x-4=-4(x+1)
b)16a²+24ab-9b²+16a²+24ab+9b²-(16a²-12ab+12ab-9b²)=16a²+24ab-9b²+16a²+24ab+9b²-16a²+12ab-12ab+9b²=
=16a²+48ab+9b²
=x²+2x-2x-4-x²-4x-4= -4x-4=-4(x+1)
b)16a²+24ab-9b²+16a²+24ab+9b²-(16a²-12ab+12ab-9b²)=16a²+24ab-9b²+16a²+24ab+9b²-16a²+12ab-12ab+9b²=
=16a²+48ab+9b²
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Ed. muzicală,
9 ani în urmă
Ed. muzicală,
9 ani în urmă